A Logit Test of Turnover Intentions of Teachers Professionals. The Role of HRM Practices and Community Embeddedness in Public Secondary Schools in Murang’a County Kenya - Kamau, Onesmus M.; Muathe, Stephen M. A.; Wainaina, Lawrence (European Scientific Journal, ESJ, 2020)
The problem of turnover intentions has continued to draw the interest of researchers, HR practitioners and employers. However the moderating role of community embeddedness in the relationship between Human Resource Management (HRM) practices and turnover intentions has received little attention. The study thus sought to investigate the moderating effect of community embeddedness in the relationship between HRM practices and turnover intention of teachers in public secondary schools in Murang’a county Kenya. The study was guided by the Social Exchange, Theory (SET) and Job Embeddedness Theory. The target population was 3752 Teachers Service Commission (TSC) teachers in 304 public secondary schools in Murang’a county Kenya. The study used multi stage random and purposive sampling methods to select a sample size of 400 teachers. A self-administered semistructured questionnaire was used to collect data. The quantitative data was analysed using descriptive and inferential statistics. The findings of the study indicated that community embeddedness moderates the relationship between HRM Practices and turnover intentions of teachers in public secondary schools in Murang’a county Kenya. The study thus concluded that community embeddedness plays an important role in turnover intentions decision of teachers.